Glutamine-driven metabolic reprogramming promotes CAR-T cell function through mTOR-SREBP2 mediated HMGCS1 upregulation in ovarian cancer - Jiannan Chen; Lianfeng Zhao; Wenying Li; Shuai Wang; Jiayi Li; Zhongyuan Lv; Yaoyao Zhao; Junqing Liang; Zhigang Hu; Feiyan Pan; Lingfeng He; Lili Gu; et al. (Journal of Translational Medicine)
Abstract Background Chimeric antigen receptor T (CAR-T) cell therapy holds promise for cancer treatment, but its efficacy is often hindered by metabolic constraints in the tumor microenvironment. This study investigates the role of glutamine in enhancing CAR-T cell function against ovarian cancer. Methods Metabolomic profiling of blood samples from ovarian cancer patients treated with MSLN-CAR-T cells was conducted to identify metabolic changes. In vitro, glutamine pretreatment was applied to CAR-T cells, and their proliferation, CAR expression, tumor lysis, and cytokine production (TNF-α, IFN-γ) were assessed. Mechanistic studies focused on the mTOR-SREBP2 pathway and its effect on HMGCS1 expression, membrane stability and immune synapse formation. In vivo, the antitumor effects and memory phenotype of glutamine-pretreated CAR-T cells were evaluated. Results Elevated glutamine levels were observed in the blood of ovarian cancer patients who responded to MSLN-CAR-T cell treatment. Glutamine pretreatment enhanced CAR-T cell proliferation, CAR expression, tumor lysis, and cytokine production. Mechanistically, glutamine activated the mTOR-SREBP2 pathway, upregulating HMGCS1 and promoting membrane stability and immune synapse formation. In vivo, glutamine-pretreated CAR-T cells exhibited superior tumor infiltration, sustained antitumor activity, and preserved memory subsets. Conclusions Our findings highlight glutamine-driven metabolic rewiring via the mTOR-SREBP2-HMGCS1 axis as a strategy to augment CAR-T cell efficacy in ovarian cancer. Trial registration NCT05372692